2017
DOI: 10.1002/ece3.3333
|View full text |Cite
|
Sign up to set email alerts
|

Thermal plasticity in postembryonic life history traits of a widely distributed Collembola: Effects of macroclimate and microhabitat on genotypic differences

Abstract: Life history traits in many ectotherms show complex patterns of variation among conspecific populations sampled along wide latitudinal or climatic gradients. However, few studies have assessed whether these patterns can be explained better by thermal reaction norms of multiple life history traits, covering major aspects of the life cycle. In this study, we compared five populations of a Holarctic, numerically dominant soil microarthropod species, Folsomia quadrioculata, sampled from a wide latitudinal gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 70 publications
(136 reference statements)
1
20
0
Order By: Relevance
“…Folsomia quadrioculata was extracted without heating in 2007 from randomly collected soil samples from the small northernmost island of Svalbard, Norway (Little Slate Island; 80.321°N, 20.360°E). This population belongs to a presumably highly pristine environment, and its life-history traits have been studied in detail previously (Sengupta et al 2016(Sengupta et al , 2017. The animals were reared in small plastic boxes (diameter 3.4 cm, height 3 cm) with a moist base made of plaster of Paris and charcoal (Sengupta et al 2016).…”
Section: Test Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Folsomia quadrioculata was extracted without heating in 2007 from randomly collected soil samples from the small northernmost island of Svalbard, Norway (Little Slate Island; 80.321°N, 20.360°E). This population belongs to a presumably highly pristine environment, and its life-history traits have been studied in detail previously (Sengupta et al 2016(Sengupta et al , 2017. The animals were reared in small plastic boxes (diameter 3.4 cm, height 3 cm) with a moist base made of plaster of Paris and charcoal (Sengupta et al 2016).…”
Section: Test Organismsmentioning
confidence: 99%
“…Folsomia quadrioculata (Tullberg 1871) is a widely distributed collembolan, which is abundant in diverse habitat types across the northern hemisphere (Fjellberg 1994;Deharveng and Lek 1995;Ponge 2000). It reproduces sexually, and populations from different geographical regions and habitat types are known to differ in terms of thermal adaptation in several life-history traits (Sengupta et al 2016(Sengupta et al , 2017. The temperature responses of F. quadrioculata populations suggest that an assessment of responses in multiple traits is essential for providing ecologically accurate explanations.…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic plasticity can be adaptive and has been reported to improve survival in Lepidoptera (Stotter and Terblanche, 2009;Chidawanyika and Terblanche, 2011a;Fischer et al, 2010;Mutamiswa et al, 2018a), Diptera (Overgaard and Sørensen, 2008;Kalosaka et al, 2009;, Coleoptera (Chidawanyika et al, 2017;Nyamukondiwa et al, 2018) and related taxon e.g. Collembola (see Chown et al, 2007;Sengupta et al, 2017). Studies have also shown that phenotypic plasticity varies across ontogeny (Marais and Chown, 2008) and that immobile stages generally have inherent higher plasticity to compensate for their inability to behaviorally adapt through seeking benign microhabitats.…”
Section: Introductionmentioning
confidence: 99%
“…Adults reproduce throughout the season whenever temperature permits (Sengupta et al. ). In the Arctic, the life cycle typically extends over more than one year (Birkemoe and Sømme ), and in heterogeneous habitats, it may show strongly aggregated distribution (Hertzberg et al.…”
Section: Methodsmentioning
confidence: 99%
“…It is a typical litter-dwelling (hemiedaphic) drought-sensitive species (Hertzberg and Leinaas 1998) and shows limited ability to move across open surfaces (Hertzberg et al 1994). Adults reproduce throughout the season whenever temperature permits (Sengupta et al 2017). In the Arctic, the life cycle typically extends over more than one year (Birkemoe and Sømme 1998), and in heterogeneous habitats, it may show strongly aggregated distribution (Hertzberg et al 1994).…”
Section: Study Speciesmentioning
confidence: 99%